Potent induction of apoptosis by givinostat in BCR-ABL1-positive and BCR-ABL1-negative precursor B-cell acute lymphoblastic leukemia cell lines. (September 2017) - Yao, Chenjiao; Zhang, Guojuan; Walker, Alison; Zhao, Kevin Y.; Li, Ying; Lyu, Lei; Tang, Yan; Ru, Peng; Jones, Dan; Zhao, Weiqiang
Highlights: Givinostat induced potent apoptosis in B-cell lymphoblastic leukemia cells with different genetic background. The mechanism of apoptosis induction relies on intact TP53 expression and p21. Alternative mechanism of apoptosis is proposed. Abstract: We have previously shown that givinostat can induce potent apoptosis in the BCR-ABL1 -positive, TP53 -wild type B-cell acute lymphoblastic leukemia (B-ALL) cell line SUP-B15. We extend our studies here to two additional B-ALL cell lines, BCR-ABL1 -negative CCRF-SB and p210 BCR-ABL1 -positive NAML1. Givinostat induced significant cell growth inhibition in both cell lines, with an IC50 of 0.65 ± 0.052 μM and 0.25 ± 0.028 μM in CCRF-SB and NAML1, respectively. The key signal protein of the BCR-ABL1, Crk-L1, was significantly reduced by givinostat treatment in NAML1. As in SUP-B15, givinostat induced apoptosis in both cell lines but showed different levels of cleavage of the procaspase proteins Casp-3, Casp-7 and PARP. Levels of cell cycle-DNA repair regulator p21, CHK1 and FANCD2 levels were markedly affected by givinostat treatment. These data further enrich our understanding of the mechanisms of the antineoplastic effects of givinostat in B-ALL and provide a preclinical rationale for the inclusion of givinostat or similar agent in leukemia therapy.